STRATEGI PEMBINAAN TILAWATIL QUR’AN DI KABUPATEN TANGERANG - Fauzi, Anis; Zohriah, Anis; Qurtubi, Ahmad; Supardi, Supardi (Universitas Kadiri, 2023)
The rise of Tilawatil Qur'an extracurricular activities in the Daar El Syahid Islamic Boarding School has received appreciation from the local government of Tangerang Regency to be used as a place for coaching and forming Qori and Qoriah cadres for the government and people of Tangerang Regency. The success of the Daar El Syahid Islamic Boarding School management in collaborating with the Regional Government of Tangerang Regency, as well as in fostering student cadres who pursue the field of Tilawatil Quran is a serious concern for managers of the Islamic Education Management Study Program (S-2) to find out and understand the procedures and ins and outs of the student development program who have extraordinary talents and interests in the field of Tilawatil Qur'an. most of the students of Daar El Syahid Islamic Boarding School, who are also students of SMP Labschool Tangerang and SMK Labschiol Tangerang actively participate as caravans in the Musabaqoh Tiawatil Qor'an arena at the Tangerang Regency level and Banten Province level.